(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study investigates the difficulties Uzbek learners face in developing English writing skills due to the absence of grammatical gender. Uzbek does not mark gender in pronouns or nouns, while English requires correct use of he, she, and it. These structural differences often lead to pronoun errors, lack of clarity, and reduced writing fluency. The study involved intermediate-level Uzbek EFL learners and collected data through short writing tasks, paragraph exercises, and semi-structured interviews. Findings show that first language transfer causes frequent pronoun mistakes and unclear references. Two teaching methods—contrastive pronoun awareness activities and structured guided writing tasks—were found to improve learners’ accuracy, clarity, and confidence in writing. Addressing grammatical gender differences directly in teaching is essential for enhancing English writing skills among Uzbek learners.